2020
DOI: 10.3389/fmicb.2020.00812
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B and Vitamin C Affect DNA Methylation and Amino Acid Metabolism in Mycobacterium bovis BCG

Abstract: Vitamins are essential nutrients and key cofactors of enzymes that regulate cellular metabolism, and also activate the immune system. Recent studies have shown that vitamin B1 (V B1 ) and vitamin C (Vc) can inhibit Mycobacterium tuberculosis growth, but the precise mechanism is still not well understood. In the present study, we have used RNA-sequencing (RNA-seq), liquid chromatography coupled to mass spectrometry (LC-MS) and single-molecule real-time (SMRT) sequencing to analyze the transcriptional, metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Recently, scholars 38 have found that VB6 is related to the metabolism of H 2 S, H 2 S 2 , cystine, cysteine, homocysteine, cystine sulfide, and methionine in the metabolic reprogramming of liver cancer. 39 Many clinical trials 40–42 have observed an anti-hepatocellular carcinoma effect by directly supplementing VB6, and some studies reported negative results. In the present study, we constructed a mouse model of chronic liver injury by CCl4 and treated these mice with VB6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, scholars 38 have found that VB6 is related to the metabolism of H 2 S, H 2 S 2 , cystine, cysteine, homocysteine, cystine sulfide, and methionine in the metabolic reprogramming of liver cancer. 39 Many clinical trials 40–42 have observed an anti-hepatocellular carcinoma effect by directly supplementing VB6, and some studies reported negative results. In the present study, we constructed a mouse model of chronic liver injury by CCl4 and treated these mice with VB6.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, scholars 38 have found that VB6 is related to the metabolism of H 2 S, H 2 S 2 , cystine, cysteine, homocysteine, cystine sulfide, and methionine in the metabolic reprogramming of liver cancer. 39 Many clinical trials [40][41][42] have observed an anti-hepatocellular carcinoma effect by directly…”
mentioning
confidence: 99%
“…Iron had a similar but insignificant effect. The reason could be that Zn is an inorganic element, which can activate enzyme activity (C. Li, 2015), and amino acids are organic substances, with their metabolic pathways also affected by other organic substances such as vitamins (N. Song, Zhu, et al., 2020). Zinc may combine with the functional groups of amino acids, destroy the molecular structure of amino acids, and affect the chemical processes such as hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, with advancement of microbial genomics, it may be possible to utilize vitamins to target DNA/RNA so as to prevent growth and cause death 65,66 . Example, vitamins B and C can interfere with the normal DNA methylation causing reduced thermodynamic stability and expression of the restriction modification system of Mycobacterium bovis (BCG) 67 . Vitamin B 12 serve as a nonpeptidic carrier for peptide nucleic acid to target the messenger RNA so as to inhibit gene expression in E. coli 68 .…”
Section: Vitamins and Genomic Influence On Resistant Microbial Agentsmentioning
confidence: 99%